Applications for Bacteriophage Therapy during Pregnancy and the Perinatal Period - Furfaro, Lucy L.; Chang, Barbara J.; Payne, Matthew S. (Frontiers in Microbiology, 2018)
Pregnant women and their unborn children are a population that is particularly vulnerable to bacterial infection. Physiological changes that occur during pregnancy affect the way women respond to such infections and the options that clinicians have for treatment. Antibiotics are still considered the best option for active infections and a suitable prophylaxis for prevention of potential infections, such as vaginal/rectal Streptococcus agalactiae colonisation prior to birth. The effect of such antibiotic use on the developing fetus, however, is still largely unknown. Recent research has suggested that the fetal gut microbiota plays a critical role in fetal immunologic programming. Hence, even minor alterations in this microbiota may have potentially significant downstream effects. An ideal antibacterial therapeutic for administration during pregnancy would be one that is highly specific for its target, leaving the surrounding microbiota intact. This review first provides a basic overview of the challenges a clinician faces when administering therapeutics to a pregnant patient and then goes on to explore common bacterial infections in pregnancy, use of antibiotics for treatment/prevention of such infections and the consequences of such treatment for the mother and infant. With this background established, the review then explores the potential for use of bacteriophage (phage) therapy as an alternative to antibiotics during the antenatal period. Many previous reviews have highlighted the revitalisation of and potential for phage therapy for treatment of a range of bacterial infections, particularly in the context of the increasing threat of widespread antibiotic resistance. However, information on the potential for the use of phage therapeutics in pregnancy is lacking. This review aims to provide a thorough overview of studies of this nature and discuss the feasibility of bacteriophage use during pregnancy to treat and/or prevent bacterial infections.